3G handy guide : electrician - 3G E-Learning.; 3G E-Learning. (United States of America : 3G E-Learning, 2023)
Electrician: roles and responsibilities--Useful tools and equipment--Electricity safety practices--Wiring systems and types--Bonding and grounding--Climb pole.
Includes references, glossary, and index.
Keywords: Electrical engineering -- Vocational guidance